Healthcare Insurance Agreement Regarding Financing of Health Services by Insurance Companies - Dewi Novia Laras; Hanna Yulita; Muhamad Ikhsan; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
This study analyzes health insurance as a form of financial protection designed to reduce the burden of medical costs when a participant experiences a health problem. In practice, the relationship between the participant and the insurance provider is based on a legal agreement called an insurance contract. This contract is legally binding on both parties: the insurer (insurance company) and the insured (insurance participant), and includes rights and obligations that must be fulfilled during the coverage period. In Indonesia, public understanding of health insurance contracts remains relatively low. Many participants do not fully understand the content and implications of the agreement they sign, including the terms and conditions, guaranteed benefits, coverage limits, and claims procedures. This approach was chosen to gain a comprehensive understanding of the patterns, causal factors, and impacts of agreement health insurance reported in various cross-country studies and insurance schemes, both public, private, and community-based health insurance contracts, whether administered by social institutions like BPJS Kesehatan (Social Security Agency for Health), or by commercial insurance companies, have different structures and provisions. Problems gap arise when participants lack detailed knowledge of the scope and limitations of their insurance contracts, resulting in underutilization of available benefits. Furthermore, from the service provider's perspective, contract implementation often faces administrative and communication challenges, which can impact participant satisfaction and perceptions of service quality. The result of study is important to examine more deeply the content and implementation of health insurance contracts, as well as the extent to which participants understand their rights and obligations. A better understanding of insurance contracts will improve the effectiveness of health protection and strengthen public trust in the Indonesian health insurance system.